The Immanent Critique of Yuly Aikhenvald: Silhouettes of Gogol and Dostoyevsky - Oksana A. Kravchenko; Zeinab Sadeghi Sahlabad (Studia Litterarum)
The article is devoted to the study of the key motifs of the essays “Gogol” and “Dostoevsky” in the collection “Silhouettes of Russian Writers” by Yu. Aikhenvald. The Author analyzes the receptive attitudes of immanent criticism, which presupposes a superhistorical existence of artistic meanings. The article proposes to extend the system of Russian literature concentres developed by Aikhenvald by a methodologically significant opposition between Pushkin’s and Gogol’s traditions. In the context of this opposition the article describes the line of continuity between Gogol and Dostoevsky, and shows that the Gogol’s comedy and Dostoyevsky’s tragedy are equally opposed to the harmony of Pushkin’s work. The authors analyses key motifs linking Gogol’s and Dostoevsky’s essays: madness, deadness, crime, night consciousness, lack of faith in man; and also reflects on allusions to Dante’s “The Divine Comedy.” The article shows that the call to overcome the influence of Dostoevsky is providentially reflected in the biography of Aikhenvald, a passenger of the “philosophical steamship” who left Russia in 1922. The author concludes that the dominant role of Gogol’s and Dostoyevsky’s line in the critic’s assessment of Russian cultural perspectives is obvious.